زيادة الإتقان لحفظ المفردات العربية علي سبيل تطبيق أسلوب تذكير المحاكاة للطلاب غير الناطقين بهاBahasa Arab - Fakron Jamalin; Iva Hidayati (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2021)
This paper begins with the lack of Arabic competence among the students who enter the elementary Islamic school in Madarasah Diniyah al-Karomah Malang. Mastering the Arabic vocabularies is the first skill to comprehend with but most of the students lack of it. So these paper focused on (1) How is the application of the Mimicry Memorization Method (Mim Mem Method) to the vocabulary learning in 1st class of Madrasah Diniyah Al-Karomah (2) How is the effectiveness of using the Mimicry Memorization Method (Mim Mem Method) in the mastery of Arabic vocabulary students in 1st class of Madrasah Diniyah Al-Karomah. This research used a Classroom Action Research (CAR). This research was conducted in two cycles which were carried out from March to July 2020. Research data obtained from quantitative data. Then the quantitative data in the form of observations, questionnaires, and student test scores for each cycle were analyzed using percentage techniques and descriptive statistics. The results of this study, In the pre-test students obtained an average score of 56 then after post-test in first cycle increased to 73,4. In the post-test of second cycle the students' average score increased again to 75. The increase was also seen in the results of observations of learning activities during the four meetings. The increase in learning activities increased from 95% to 96%.